Social support as a predictor of depressive symptoms and quality of life among women with coronary heart disease post hospitalization - Sharmini Abd Karim (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2007)
The aim of this research was to examine the relationship between social support and depressive symptoms and quality of life among women with coronary heart disease post hospitalization. Research in this area indicated that lack of social support contributed to depression and poor quality of life after one is treated for heart disease, thus affecting recovery and prognosis. Though this is the situation, research focused on women is scarce. Therefore there is a need to understand the condition of women with CHD in Malaysia. Three types of social support were studied; physical support, emotional support and informational support. It was hypothesized that (a) the more support received the less depressive symptoms reported, and (b) the more support received the better the quality of life. Coping strategy was hypothesized to moderate the relationship between social support and the outcomes. Sixty women above 40 years old, who were attending follow-up clinic at the National Heart Institute, Kuala Lumpur, were interviewed. Fifty were interviewed using a questionnaire containing items from the scales mentioned here, while the other ten were interviewed using an open-ended questionnaire meant for a qualitative analysis. Instruments used in this research were Social Support Scale (Sherbourne & Stewart, 1991), COPE (Carver & Weintraub, 1989), Hospital Anxiety and Depression Scale (HADS) (Zigmond & Snaith, 1983) and the MacNew Heart Disease Health Related Quality of Life Questionnaire (Oldridge & Lynette, 2000). Results of the research showed that informational support significantly predicted depressive symptoms, but not quality of life. Problem-focused coping moderates the relationship between informational support and depressive symptoms and quality of life. Qualitative analysis revealed that social support improves quality of life and enhances emotional well-being. The findings of this study may have implications in the design of cardiac rehabilitation programmes in Malaysia.